SHORT HISTORICAL NOTES XXIII - Anton Gajdoš; Michal Bábela (University of Ljubljana Press (Založba Univerze v Ljubljani), 2022)
Ph.D. Anton Gajdoš born on 1.6.1940 in Dubriniči (today Ukraine) lives most of his life in Bratislava (ex TCH, nowadays SVK). He comes from gymnastics family (his brother Pavel have world championship medals) and he devoted his life to gymnastics. His last achievement is establishment of Narodna encyklopedia športu Slovenska (www.sportency.sk). Among his passion is collecting photos and signatures of gymnasts. As we tend to forget old champions and important gymnasts, judges and coaches, we decided to publish part of his archive under title Short historical notes. All information on these pages is from Anton's archives and collected through years. Short historical Notes XXIII were written in collaboration with  Michal Bábela, PhD.